Spiritual captive: examining the parallels between slavery and religion in The Color Purple. - Tay, Cheryl Shuyuan. (2011)
In Alice Walker’s The Color Purple, we follow Celie’s quest for selfhood and independence through her letters addressed first to God and later to her sister Nettie. Her letters are the only time we hear her voice and thus they reveal her point of view otherwise unexpressed as she is oppressed by first Pa and then Albert. The events narrated in Celie’s voice resonate in this epistolary novel with the tropes of the slave narrative genre, from her rape by Pa to the way Celie is married off to Albert. While critics have referred to The Color Purple as a modern slave narrative, it is interesting that Walker chose to write a slave narrative in the form of correspondence that is set 60 years after slavery has ended. Hence this essay will examine how the slave narrative is retold in The Color Purple also how Walker brings to our attention the unlikely parallels between two often conflicting subjects: slavery and religion, and postulate what her intentions for doing so are. Rather than finding reprieve from her plight through prayer, Celie discovers her own sense of freedom through the rejection of Christianity when she realizes that she had “been too busy thinking bout (that old white man that she) never truly notice nothing God make” (177). To Celie, her initial religion – Christianity – did not represent a form of liberation to her, nor was it a way to reclaim her human rights. Instead it was an oppressive force that made her believe that she had no right to express and assert herself, and smothered her with rules that she felt bound to follow even without understanding why.This critical view of a religion has more in common with the view of slavery that the authors of slave narratives adopt than one would expect and begs the question of what Walker hoped to achieve in juxtaposing these two methods of oppression (for lack of a better term) in The Color Purple.